Is it Necessary to Accurately Know the Response of Facial Soft Tissues to Bone Movement in Orthognatic/Orthofacial Surgery? (International Journal of Medical and Surgical Sciences, 2014)
Orthognatic and orthofacial surgery contains procedures designed to correct skeletal facial anomalies, presenting clear aesthetic and functional orientations. Outcomes have demonstrated that the technique is efficient in the short and long terms; nowadays, orthognatic surgery is common in facial surgical practice. Nevertheless, the aesthetic aspects of the indication and results of the surgery make accurate planning a challenge, raising doubts in terms of recognizing the real soft tissue response to the movement produced at bone level. A prospective, multicenter study will be necessary to define this clinical situation? This brief review is an example of how necessary to study new methodologies about the response of soft tissue to bone movements.
Keywords: Orthognathic Surgery; Facial Surgery; Soft/Hard Tissue Ratio